2021
DOI: 10.3390/ijms22084105
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulated Immunological Functionome and Dysfunctional Metabolic Pathway Recognized for the Pathogenesis of Borderline Ovarian Tumors by Integrative Polygenic Analytics

Abstract: The pathogenesis and molecular mechanisms of ovarian low malignant potential (LMP) tumors or borderline ovarian tumors (BOTs) have not been fully elucidated to date. Surgery remains the cornerstone of treatment for this disease, and diagnosis is mainly made by histopathology to date. However, there is no integrated analysis investigating the tumorigenesis of BOTs with open experimental data. Therefore, we first utilized a functionome-based speculative model from the aggregated obtainable datasets to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…In our experiments, we also identified 13 highly relevant DEGs. Many related studies have examined how these DEGs affected the formation of serous ovarian tumors, such as tyrosine kinase related DEGs ( PTK2B , KIT , and SRC ) [ 74 , 75 , 76 ], crucial factors known to be related to tumorigenesis ( AKT1 , MTOR , MAPK3 ) [ 64 , 77 , 78 , 79 , 80 ], DEGs related to cellular metabolism and immunity ( EDN1 , IL1B , INS , APP , LEP ) [ 29 , 56 , 60 , 81 , 82 , 83 , 84 , 85 , 86 ], and agents for signal transmission and channels of cell membranes ( CDK5 and ATP1B1 ) [ 59 , 87 , 88 ]. Among these DEGs, we found that SRC has consistently poor effects on the survival of serous ovarian carcinoma patients with a poor prognosis of PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experiments, we also identified 13 highly relevant DEGs. Many related studies have examined how these DEGs affected the formation of serous ovarian tumors, such as tyrosine kinase related DEGs ( PTK2B , KIT , and SRC ) [ 74 , 75 , 76 ], crucial factors known to be related to tumorigenesis ( AKT1 , MTOR , MAPK3 ) [ 64 , 77 , 78 , 79 , 80 ], DEGs related to cellular metabolism and immunity ( EDN1 , IL1B , INS , APP , LEP ) [ 29 , 56 , 60 , 81 , 82 , 83 , 84 , 85 , 86 ], and agents for signal transmission and channels of cell membranes ( CDK5 and ATP1B1 ) [ 59 , 87 , 88 ]. Among these DEGs, we found that SRC has consistently poor effects on the survival of serous ovarian carcinoma patients with a poor prognosis of PFS and OS.…”
Section: Discussionmentioning
confidence: 99%
“…GSR indices were calculated and extracted from the gene expression datasets by modifying the differential rank retention (DIRAC) algorithm [ 65 ] and used to measure sequential changes among the gene elements in the gene set datasets of the gene expression profiles of serous BOTs, all stages of serous ovarian carcinomas, and the most common gene expression ordering from the normal control samples. The details and calculation process of the GSR model were described in our previous studied papers [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. The microarray-based gene expression profiles from serous ovarian tumors and normal ovarian samples obtained from the GEO database were produced using the corresponding gene expression levels constructed according to the genetic elements in the GO-based functionome, which were then con-verted into ordered data based on each expression level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation